2009
DOI: 10.1177/1533317509341465
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dementia Patient’s Physical, Cognitive, and Emotional/ Behavioral Problems on Caregiver Well-Being: Findings From a Spanish-Speaking Sample From Colombia, South America

Abstract: The current study aims to (1) determine whether there is a relationship between the problems of patients with dementia and the psychosocial functioning of the caregiver, (2) determine whether these relationships exist independent of sociodemographic and caregiving-related variables, and (3) determine which type of problems of patients with dementia best predict the psychosocial functioning of the caregiver. In all, 73 family caregivers were recruited from Bogota, Colombia. The caregivers completed a checklist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
37
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 105 publications
(161 reference statements)
6
37
0
5
Order By: Relevance
“…Research has also shown that caring for relatives with dementia is a long-term and stressful experience and can impair the HRQoL of family caregivers [6,7,8,9,10]. For service providers, improving HRQoL is an indispensable part of determining effective interventions for the vulnerable population.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has also shown that caring for relatives with dementia is a long-term and stressful experience and can impair the HRQoL of family caregivers [6,7,8,9,10]. For service providers, improving HRQoL is an indispensable part of determining effective interventions for the vulnerable population.…”
Section: Introductionmentioning
confidence: 99%
“…Dementia-related impairments [8,9,10] of care recipients (CR) including cognitive and physical impairments as well as behavioral and psychological symptoms of dementia (BPSD) [12,13] and the social support for caregivers [14] are two external factors that have been reported to be strong predictors of HRQoL. The impairments of CR, particularly BPSD that can increase caregiver burden [6,9,10,15,16,17], were found to be detrimental to caregivers' HRQoL [9,18]. Social support has been regarded as an influential buffer in dealing with the stressful task of caring for a family member with dementia [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tales consideraciones se confirman en muestras de cuidadores, pues se ha encontrado que altos niveles de apoyo, se corresponden con mejores niveles salud y bienestar (Reid, Stajduhar & Chappell, 2010;Steiner et al, 2008), mitiga la vivencia de emociones negativas (Crespo & López, 2007) tales como la ira (Márquez-González et al, 2010), estrés (Betrabet, 2009;Lavela & Ather, 2010), sobrecarga, depresión y ansiedad (Arango-Lasprilla, Moreno, Rogers & Francis, 2009;Pearce & Singer, 2006;Rodríguez-Agudelo et al, 2010). En suma, el apoyo social percibido por los cuidadores familiares de adultos mayores refleja la ayuda que este recibe y facilita el ajuste, aligera la carga objetiva y subjetiva de las demandas del cuidado, aumenta las experiencias emocionales satisfactorias, contribuyendo significativamente a su crecimiento personal (Fernández-Lansac & Crespo, 2011).…”
unclassified
“…In dementia caregiving, caregivers are overwhelm with multitask activities which include activities of care, personal and family matters. As a result they will suffer from physical health problems such as chronic backache, musculoskeletal pain, reduce social activities, poor mental health, cardiovascular problems and poor sleep [6,7,8] . Previous studies have shown that these symptoms will give an impact on their quality of life [9,10,11] .…”
Section: Imentioning
confidence: 99%